Harmonizing success: unraveling the interplay of principal entrepreneurial leadership, teacher efficacy, and organizational effectiveness in English training institutions of China - Jinke, Li; Aziz, Nor Azni Abdul; Kadir, Suhaida Abdul (Frontiers in Education, 2024)
For a long time, teacher efficacy and organizational effectiveness have been researched in primary, junior high schools or university settings. Training institutions are a special type of profit-making educational organization, there is relatively little research conducted on them. Entrepreneurial leadership is an innovative leadership concept that, to some extent, contributes to improving teacher efficacy and organizational effectiveness, which is rarely studied in the educational domain. In accordance with the tenets of the open social system theory, this study proposed a model that teacher efficacy has a mediation effect on principal entrepreneurial leadership and organizational effectiveness. To evaluate the proposed model and explore the relationships among principal entrepreneurial leadership, teacher efficacy and organizational effectiveness, this study researched 381 teachers in English training institutions via Pearson correlation analysis and mediation effect analysis. The findings showed that positive and significant relations among principal entrepreneurial leadership, teacher efficacy and organizational effectiveness, and confirmed that teacher efficacy has a mediating effect on principal entrepreneurial leadership and organizational effectiveness in training institutions. These findings contributed to expanding the implementation of open social system theory from the three perspectives, providing new comprehension for government educational departments, principals and teachers in the organizational effectiveness of training institutions.